A fractional-order model on the dynamic mechanical behavior of magnetorheological elastomers. (17th January 2020) - Zhu, Guanghong; Xiong, Yeping; Li, Zigang; Li, Ming; Bai, Xianxu 'Frank'
Abstract: In order to describe the dynamic behavior of magnetorheological elastomers (MREs) for the realization of vibration control, this study proposes a constitutive model containing a fractional element and nonlinear springs attributed to the viscoelastic and the rheological properties, respectively. The viscoelastic behavior in various magnetic fields was studied experimentally to develop this fractional-order nonlinear model, and the model parameters were identified through experimental data fitting of dynamic modulus in frequency domain. The model predictions were subsequently obtained with the predictor-corrector approach to validate the proposed model by comparing with the experimental results on the stress-strain hysteresis. In addition, the efficiency of the proposed model of MRE was also evaluated by comparing the numerical solution with the results of the revised Bouc–Wen model.